Mothers Initial Challenges Having Children with Autism Spectrum Disorders in Bangladesh (Bangladesh Journal of Medical Science, 2020)
Background: Autism, one of the most widespread problems in the world, is rising alarmingly in Bangladesh day by day. Over the most decade autism has become one of the most visible and articulated social issues in Bangladesh. Besides, in our country, journey of a mother with a special child is a challenge.Objectives: To find out the experiences and challenges of mothers having children with ASDs.Materials and Methods: The study was based on case study method where 20 mothers were selected purposively from Dhaka division. Data was collected using an open ended questionnaire and in depth interviews.Results: In this study though majority of the mothers reported having a typical pregnancy with little or no complications. Majority of the mothers had no knowledge about autism before. The average age of children when they diagnosed was 2.9 years. In response to their initial reactions to diagnosis of their child, mothers reported the following emotional states: shock, depression, self-blamed, sadness. Prayer was a clear coping strategy for parents of an autistic child. Most of the mothers reported passing many days with depression and frustration. All the mothers were satisfied with the activities of the current special school.Conclusion: Mothers reported about their most challenging part of raising their autistic child were to manage their hyperactivity and social interaction. They realize a strong familial and social support are necessary as it was found as a key factor in adjusting and coping a mother to her challenging life with her autistic child.Bangladesh Journal of Medical Science Vol.19(2) 2020 p.268-272